Landasan-landasan Teoretis dalam Bimbingan dan Konseling: Pilar Filosofis, Psikologis, Sosial Budaya, Iptek dan Religius - Cici Saputri; Al Hamida; Dini Gita Sartika; Royhana Safitri; Dinda Putri Hasanah; Salsa Bila Khotrun Nada; Wardah Yuni Kartika (Universitas Muhammadiyah Metro, 2025)
Guidance and counseling are among the essential aspects of education, serving to support students’ comprehensive development. To ensure that counseling services are delivered professionally and contextually, a strong understanding of their theoretical foundations is required. This article outlines five main pillars that underpin counseling practices: philosophical, psychological, socio-cultural, scientific-technological, and religious dimensions. Each foundation contributes uniquely to shaping a holistic counseling approach. The integration of these five dimensions results in counseling services that are relevant, comprehensive, and responsive to students needs.